Towards the CYcle ROute Network of the MEDiterranean. The CYRONMED project - Sforza, Raffaele (TeMA - Journal of Land Use, Mobility and Environment, 2008)
In Southern European areas, cycling is more limited for the absence of cycling infrastructure; for too much motorised traffic on the roads; for the absence of land set aside for non-motorised transport; for the absence/shortage of transport links between bikes and public transport (bus / train / boat / aeroplane). Starting from this framework, Regione Puglia coordinates the CYRONMED project, whose aim is to supporting cycling and investing money in better infrastructures in order to implement sustainable policies to fight climate change. The paper describes the main result of the CYRONMED project in Regione Puglia. The project concerns a feasibility study of cycle paths in South-Eastern Mediterranean areas, linking train stations, sea ports, and airports; processing and publication of a technical manual to bring such a cycle network to fruition; a study about the strategy of tourism by bike advancement and development in Archimed area; a study about the strategy to advance and develop bicycle tourism in the ARCHIMED area. The expected results concerns promoting urban mobility and cycle-tourism in the in Archimed Area with Eurovelo and Bicitalia; to promote international cooperation, dialogue, and the exchange of experiences between the various authorities in order to reach a consensus on standards required for cycling infrastructures; by establishing a standard methodology for implementing cycling infrastructures, tools could be developed to assist the relevant planning in the interested countries or regions.